Scalar-tensor Theory LG = ϕR − 2γϕη and the Problem of Dark Matter - Anh Ky, Nguyen; Ky, Pham Van (VNU Journal of Science: Mathematics - Physics, 2022)
Searching for the origin of the dark matter and the dark energy is among the problems that the modern physics, including the general theory of relativity, is facing to. Various theories or models have been proposed to solve these problems without satisfactory success yet. In this work, a new model based on the scalar-tensor theory with Lagrangian L G = ϕR − 2 γϕ η is suggested to solve some aspects of the above-mentioned problems. In this model the dark matter is interpreted as geometric background of the space-time.